2013
DOI: 10.1039/c3dt51771c
|View full text |Cite
|
Sign up to set email alerts
|

Zinc(ii), iron(ii/iii) and ruthenium(ii) complexes of o-phenylenediamine derivatives: oxidative dehydrogenation and photoluminescence

Abstract: Reactions of benzoyl pyridine, o-phenylenediamine and anhydrous ZnX2 in methanol afford imine complexes [Zn(L1)X2] (X = Cl, 1; X = Br, 2) in good yields (L1 = (E)-N(1)-(phenyl(pyridin-2-yl)methylene)benzene-1,2-diamine). The reduction of 1 with NaBH4 affords (E)-N(1)-(phenyl(pyridine-2-yl)methylene)benzene-1,2-diamine (L2H). The reaction of L2H with [Ru(II)(PPh3)3Cl2] results in the oxidative dehydrogenation to L1 generating cis-[Ru(II)(L1)(PPh3)Cl2] (3). The reaction of L2H with salicylaldehyde affords (E)-2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 100 publications
0
9
0
Order By: Relevance
“…o-Phenylene derivatives are synthesized using the reported procedures. 7 L 3 t-Bu H 2 and 3-6 are characterized by the elemental analyses and IR, mass, EPR and 1 H NMR spectra. The VvO stretching vibrations of 3 and 4 are at 966 and 959 cm −1 , while the symmetric and asymmetric stretching vibrations of two cis MovO 25 resonate at 901 and 915 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…o-Phenylene derivatives are synthesized using the reported procedures. 7 L 3 t-Bu H 2 and 3-6 are characterized by the elemental analyses and IR, mass, EPR and 1 H NMR spectra. The VvO stretching vibrations of 3 and 4 are at 966 and 959 cm −1 , while the symmetric and asymmetric stretching vibrations of two cis MovO 25 resonate at 901 and 915 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…It was recorded that 1 has eighty fold stronger emission than L 3 H 2 itself, while the ketimine analogue 2 + ion is non-emissive. 7 The fluid solution fluorescence features of 3, 4, 5 and 6 are also recorded at 298 K. It is found that 3 and 4 in fluid solutions at 298 K are non-emissive while the electrogenerated one-electron oxidized analogues,…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations